A comparative study of surgical procedures in neonatal intestinal atresia - resection and anastomosis, Bishop Koop, Santulli and Mikulicz procedure - Basak, Aniruddha (International Journal of Contemporary Pediatrics, 2021)
Background: The aim of this work was to assess the outcome for patients with jejunoileal atresia who underwent primary anastomosis, Bishop–Koop, Santulli procedure and Mikulicz procedure. Intestinal atresia is one of the most common causes of intestinal obstruction in neonates. But ideal surgical management of this condition remains controversial. Methods: During the period from January 2017 to January 2019, 112 neonates (62 males and 50 females) suspected to have intestinal atresia were operated in NRSMCH, Kolkata. 30 patients were treated with primary resection/ anastomosis, 30 patients underwent Bishop-koop (BK) technique, 27 patients who were treated with Santulli technique and 25 patients who were treated with Mikulicz procedure. Demographics, treatment and outcomes including mortality, morbidity and nutrition status were reviewed and were compared among the four groups. Results: 20 patients (17.86%) died during the perioperative period. Among them, 10 died due to uncontrolled sepsis and 10 due to malnutrition. Mortality was highest in Primary anastomosis group (33.33%) followed by BK group (13.3%), Santulli group (11.1%) and lowest in Mikulicz group (4%). The Mikulicz group experienced the lowest re-operation rate (4%) and Primary anastomosis group experienced highest re-operation (26.7%). This difference was statistically significant (P<0.003). Conclusions: Using Mikulicz procedure in the current study has improved the survival of these patients and minimized the post-operative complications.